The organized executive [soundrecording] new way to manage time, paper and people - Winston, Stephanie (New York Simon & Schuster, 1987)
Tackles the role of an effective manager.
Keywords: Paperwork (Office practice) -- Management; Executives -- Time management; Office management; Psychology; Public administration; Management